Incidence of motor neurone disease in the northern region. Issue 1 (March 1987) - Qizilbash, N; Bates, D
Abstract : The incidence of motor neurone disease in the Northern Region was studied for the year 1981 by means of hospital activity analysis records and questionnaire. The crude incidence rate was 2.2 per 100, 000. This was not significantly different from the rate determined by using death certification. The age standardised incidence ratio for the region was 163 using the 1976 population and deaths from motor neurone disease in England and Wales as the reference. The female to male ratio was 1:1.8 and the average age of diagnosis was 63 years. No meaningful intraregional variation was observed. Thus mortality appears to reflect incidence fairly accurately.